Intersticio hídrico, plan parcial sinapsis boreal (2019)
A business centre offering a space to the people of the region, so that they have the opportunity to expose your products or innovative new stockists and so be able to generate development and competitiveness which will favour not only the region but to the progress of the country, creating; possible business, exploitation of products, labor economic growth, increase competitiveness, increase cultural level.